RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN PADA BUILDING MANAGEMENTAPARTEMENT GRAND CENTERPOINT BEKASI - Nisa Liama; Yulia Nur Rachmawati; Nani Agustina (Jupiter: Journal of Computer & Information Technology, 2023)
Payroll is very meaningful for companies or agencies so we need a system that facilitates payroll activities. Apartment Grand Centerpoint operates in the service sector in the form of flats, experiencing problems in processing employee attendance data due to the processing of attendance book data as a manual system, resulting in operational errors and irregularities in calculating and paying salaries. This research was conducted with the aim of designing a payroll system to facilitate accounting & finance in payroll in companies with system features such as managing attendance data, managing employee data along with their positions, managing payroll data, managing payroll report data, journal reports, and employee payslips.